Pembentukan dan Makna Gairaigo dalam Anime Yuru Camp Season 1 (2018) - Ayudya, Aldi Bisma; Hidayati, Yanti; Anwar, Aulia Arifbillah (Departemen Sastra Jepang, Fakultas Ilmu Budaya, Universitas Hasanuddin, 2025)
In the era of globalization, the Japanese language has increasingly absorbed foreign vocabulary, particularly English, a phenomenon known as Gairaigo. This can be observed across various fields, including in the dialogues of the anime Yuru Camp Season 1 (2018), which depicts the use of Gairaigo in outdoor activities. This study aims to analyze the formation and meaning of gairaigo in Yuru Camp Season 1 (2018) through a morphosemantic approach based on Nomoto’s (2019) theory of gairaigo formation. Gairaigo refers to vocabulary borrowed from foreign languages, particularly English, into the Japanese language. In this research, the researcher uses a descriptive qualitative method to describe and analyze the formation patterns and semantic shifts of gairaigo in the anime. Data were collected through the observation and note-taking technique from the dialogues of 12 episodes of the anime under analysis. The results show that there are 20 gairaigo data points, encompassing various formation categories such as grammatical adaptation, abbreviation, creation (wasei-gairaigo), and konshugo (a combination of wago or kango with gairaigo). The findings suggest that gairaigo in Yuru Camp is not only used in everyday conversation but also undergoes various shifts in meaning depending on the context and usage within popular culture. This study is expected to provide new insights into the role of gairaigo in audiovisual media and how its adaptation process occurs in modern Japanese language.